The lean turnaround : how business leaders use lean principles to create value and transform their company - Byrne, Art, 1945- (McGraw-Hill, 2013)
Shares what the author has learned during his remarkable career and shows how anyone can achieve similar results. This book explains the ins and outs of applying Lean strategy to: eliminate waste in every value-added operation; deliver consistent value to customers; stimulate growth and add jobs; and more.